Pale Damsel Bug Nabis capsiformis Germar (Insecta: Hemiptera: Nabidae) - Karol L. Krey; Justin M. Renkema (EDIS)
The pale damsel bug, Nabis capsiformis (Germar), one of the most widespread Nabis species, is a generalist predator that can be found in open areas, including coastal habitats (Lattin 1989). It is commonly reported throughout the southeastern United States, in a variety of ecosystems, it is particularly common in field and row crop agroecosystems. All nympal and adult life stages of Nabis capsiformis are excellent predators and can typically eat one lepidopteran egg or aphid per day when small and as many as two dozen eggs or other prey as later instars and adults. They can survive for up to two weeks without food and become cannibalistic if other prey are unavailable. They use their thickened raptorial front legs that are lined with spines to catch and hold prey, then suck out the body contents with their piercing mouthparts.